Advances in Pediatric Pharmacology, Therapeutics, and Toxicology - Gonzalez, Daniel (2014)
Significant advancements have been made in pediatric therapeutics and pharmacology over the last two years. In the United States, passage of the Food and Drug Administration Safety and Innovation Act has made the Best Pharmaceuticals for Children Act and Pediatric Research Equity Act permanent, and ensured that studies will be conducted in neonates. In Europe, the Pediatric Regulation, which went into effect in early 2007, has also provided a framework encouraging an expansion of pediatric research. Because of such regulatory involvement, a greater number of studies are being performed, and more pediatric dosing, efficacy, and safety information is being incorporated into product labels. The goal of this publication is to highlight important advancements made in the field of pediatric pharmacology, toxicology, and therapeutics from January 2012 to December 2013.